Analisis Kinerja Aparatur Sipil Negara di Lingkungan Sekretariat Daerah Kabupaten Muara Enim - Abdul Nadjib (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
At time advances in technology today, the public can directly supervise the performance of employees in government institutions., therefore the demands of working professionally must be realized in daily activities by the state civil apparatus. Considering the importance of the quality of the performance of the state civil apparatus for the progress of the nation and state, this study aims to analyze and describe how the performance of the state civil service, especially in the scope of the Regional Secretariat of Muara Enim Regency based on the specified performance indicators. This research is qualitative in nature, starting with the determination of respondents as sources of information (informants) until a descriptive analysis is carried out on the data obtained and grouped according to each indicator. The number of informants is twentyfive (25) people and the number of indicators is eight (8) items. The results showed that 59.4% of employee performance was acceptable or good, meaning that it was feasible to meet the criteria of quality of work, quantity of work, timeliness, discipline, effectiveness, independence, work in teams and responsibilities. While the remaining 40.6% of employees are rated as not having good performance. Some factors as determinants of employee performance include educational background, experience, ability to adapt, creativity, loyalty, and work ethic. There are still employees who have low competence, lack of willingness to learn, low competitiveness and lack of creativity, making employee productivity low.